Моделі процесів захисту цілісності інформаційних об’єктів з використанням коду умовних лишків. Алгоритм нулізації - Василенко, В.С. (Збірник наукових праць Інституту проблем моделювання в енергетиці ім.Г.Є.Пухова НАН України, 2010)
The models of processes of defense of integrity of information’s holding object with application of code of conditional tailings which provide high probabilities of exposure of violations of integrity and correction of the exposed curvatures are examined.